2016
DOI: 10.1097/md.0000000000004761
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive coping strategies and glaucoma progression

Abstract: The identification of modifiable risk factors for glaucoma progression is needed. Our objective was to determine whether maladaptive coping styles are associated with recent glaucoma progression or worse visual field mean deviation.A hospital-based case–control study was conducted in the Glaucoma Service of Maisonneuve-Rosemont Hospital in Montreal, Canada. Patients with primary open angle glaucoma or normal tension glaucoma with ≥4 years of follow-up and ≥5 Humphrey visual fields were included. Cases had rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…However, there is evidence that poorer glaucoma control is associated with more depressive symptoms, while depressive symptoms are in turn related to non-adherence and possibly poorer glaucoma control. Diniz-Filho et al 27 reported that fast visual field progression was associated with a greater occurrence of depressive symptoms in 102 patients with glaucoma, and Freeman et al 28 found that a maladaptive coping strategy (denial) led to a higher risk of glaucomatous progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is evidence that poorer glaucoma control is associated with more depressive symptoms, while depressive symptoms are in turn related to non-adherence and possibly poorer glaucoma control. Diniz-Filho et al 27 reported that fast visual field progression was associated with a greater occurrence of depressive symptoms in 102 patients with glaucoma, and Freeman et al 28 found that a maladaptive coping strategy (denial) led to a higher risk of glaucomatous progression.…”
Section: Discussionmentioning
confidence: 99%
“…The association of such symptoms with lack of adherence to medications previously reported 1315 and validated herein, may be due to maladaptive strategies of coping such as denial. 28 The possible consequence of faster glaucomatous progression 27 warrants attention to the glaucoma patient’s psychological status and better risk communication by eye care providers. Clinicians might consider using the VAQ or a single VAQ item to assess the patient’s glaucoma burden and possible related depression.…”
Section: Discussionmentioning
confidence: 99%
“…If an individual is resilient or susceptible to stressors depends largely on their personality. Maladaptive coping strategies and specific personality patterns are found in patients with glaucoma [98][99][100]. Mabuchi [101] observed that PAOG patients have significantly higher mean neuroticism scores (N), and agreeableness (A) as well as conscientiousness (C) were significantly lower in male POAG patients.…”
Section: Mental Stress and Personalitymentioning
confidence: 99%
“…The mean extraversion score (E) was significantly lower in female POAG patients. Freeman et al [98] observed that those patients that use denial when confronted with their first POAG diagnosis had a faster progression of the visual field loss.…”
Section: Mental Stress and Personalitymentioning
confidence: 99%
“…We assessed the association between demographic, clinical, and psychosocial factors and adherence in the periods preceding and following the onset of the pandemic. Psychosocial factors included resilience, 10 coping styles, 11 illness perception 12 and self-efficacy, 13 which have been associated with adherence and visual function.…”
mentioning
confidence: 99%